Reuse of Waste Rice Husk Ash and Expanded Polystyrene Beads as an Alternative Raw Material in Lightweight Concrete Bricks - Ling, I.H; Teo, Delsye Ching Lee (Directory of open access journals, 2011)
Nowadays, the demand for lightweight building materials has been growing worldwide. This paper presents an investigation on the use of renewable resources such as waste rice husk ash (RHA) and expanded polystyrene beads (EPS) beads as alternative raw materials for the production of lightweight concrete bricks. The RHA is used as partial cement replacement while waste EPS is used as partial aggregate replacement in the mixes. The key properties for the concrete bricks namely density, compressive strength, compliance for dimension and thermal conductivity were investigated. The mixes prepared were made of RHA of 5%, 10%, 15% and 20% as partial replacement for cement and with the same amounts of sand and EPS. A control concrete without any RHA replacement was also produced. The results showed that the samples with 10% RHA replacement not only gained the highest compressive strength compared to other samples but also complied with the class 2 requirement for load bearing bricks at 28days as specified in Malaysia Standard, MS76: 1972. In general, the results showed that the RHA EPS concrete brick has good potential as building material